2019
DOI: 10.1002/bse.2413
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high‐growth start‐ups on entrepreneurial environment based on the level of national economic development

Abstract: In this paper, we examine the relationship between the conditions of the entrepreneurial environment and high‐potential entrepreneurship according to the stage of economic development of the country. A structural equation model was designed based on data from the Global Entrepreneurship Monitor project, which contains information about 62 countries. Our results suggest that economic development and high‐potential entrepreneurship have a greater impact on the entrepreneurial ecosystem than entrepreneurial activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 78 publications
2
28
0
2
Order By: Relevance
“…Second, the perceptions of socio-economic conditions played a key role in college students' entrepreneurial motivations. This aligned with the views of scholars such as Liñán and Santos (2007), Gathungu andBaariu (2018), andMartínez-Fierro et al (2020), all of whom posited that entrepreneurial motivation is affected by socio-economic conditions to various extents and that favorable socio-economic conditions promote the formation of entrepreneurial motivation. The results of this study also confirmed that the development of entrepreneurial motivations among college students is affected by multifaceted factors such as the growth rate of the regional economy, entrepreneurial role models, the number of successful local entrepreneurs, and the cultural atmosphere.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Second, the perceptions of socio-economic conditions played a key role in college students' entrepreneurial motivations. This aligned with the views of scholars such as Liñán and Santos (2007), Gathungu andBaariu (2018), andMartínez-Fierro et al (2020), all of whom posited that entrepreneurial motivation is affected by socio-economic conditions to various extents and that favorable socio-economic conditions promote the formation of entrepreneurial motivation. The results of this study also confirmed that the development of entrepreneurial motivations among college students is affected by multifaceted factors such as the growth rate of the regional economy, entrepreneurial role models, the number of successful local entrepreneurs, and the cultural atmosphere.…”
Section: Discussionsupporting
confidence: 75%
“…Preferential measures for entrepreneurs offered by government departments in taxation, facilitation of approval processes, and optimization of entrepreneurial institutions Gnyawali and Fogged, 1994;Garcia-Cabrera et al, 2018;Nam and Hwansoo, 2019 Socio-economic conditions Level of development of the local economy, industrial structure, and urban construction; infrastructure such as transport, water supply, and electricity supply; and regional entrepreneurial culture Davidsson and Honig, 2003;Liñán and Santos, 2007;Gathungu and Baariu, 2018;Martínez-Fierro et al, 2020 Education and training Innovation and entrepreneurship education, related activities, and capacity-building training attended by entrepreneurs during their studies Turker and Selcuk, 2009;Sirbu et al, 2015;Bazan et al, 2020 Financial support Financial support obtained by entrepreneurs in sources of financing, interest-free loans, and start-up funds Kristiansen and Indarti, 2004;Welter, 2011;Yao et al, 2016 Non-financial support Assistance received by entrepreneurs in expert guidance, development opportunities, information, and resources Djankov et al, 2006;Schwartz, 2009;Gathungu and Baariu, 2018 attitudes and behaviors. Based on the above viewpoints, we hypothesized the following.…”
Section: Government Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been published that show a clear relationship between start-up activity and national economic development and competitiveness. 68 There is evidence that the relationship between entrepreneurship and economic development largely depends on the national economic environment, which is shaped by economic, institutional and socio-cultural factors, 69 combined with regulatory and tax frameworks. Start-ups with their innovative and entrepreneurial activity represent the key element for economic growth in developed countries 70 and developing countries.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, start-ups get created worldwide in the millions, because they are considered the source of rapid product development. Start-ups have significant contributions to job creation and growth at national, international, and industrial levels (Chodokufa, 2009 ; Andzelic et al, 2011 ); thus, they have significantly contributed to economic development (Martínez-Fierro et al, 2020 ). Start-ups have led to numerous innovative breakthroughs resulting in entirely new businesses (Hathaway, 2016 ).…”
Section: Introductionmentioning
confidence: 99%